Suppression of spin polarization as an indicator of QCD critical point - Sushant K. Singh; Jane Alam (European Physical Journal C: Particles and Fields, 2023)
Abstract We study the impact of the QCD critical point (CP) on the spin polarization of $$Λ $$ Λ -hyperon generated by the thermal vorticity in viscous quark gluon plasma (QGP). The equations of the relativistic causal viscous hydrodynamics have been solved numerically in (3+1) dimensions to evaluate the thermal vorticity. The effects of the CP have been incorporated through the equation of state (EoS) and the scaling behavior of the transport coefficients. We observe a significant suppression of the spin polarization around mid-rapidity region induced by the CP and propose that such changed behaviour of the spin polarization can be used to detect the CP. To the best of our knowledge this is the first study on the effects of critical point on the spin polarization in QCD matter.